Investigación biológica y psicopatología descriptiva - Berríos, Germán (1983)
The article analyses modern descriptive psychopathology, its epistemological basis and the contribution it has made to the determination of biological typologys in psychiatry. Sorne consequences of the search for reliability and validity are discussed in relation to nosographic classifications and instruments such as the DSM-1, DSM-11, PSE, etc. The author refers to the danger of closure and to the alternatives that exist for facing it. The concept of unity of analysis is discussed as well as the importance of adapting it to models of functional research that permit a multidimensional approach to psychopathology. This would permit classifications with a greater probability of having organic representation. Finally, the author points out the legitimity of the individual case approach.